COMMUNICATIVE COMPETENCE OF LAW ENFORCEMENT BODIES EMPLOYEES - Makeieva, Olena; Yefremeniuk, Ilona (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: to find out the essence, signs and requirements for the communicative competence of law enforcement officers, its role in the professional activity of law enforcement officers. Research methods: philosophical methods, analysis and synthesis, statistical, generalization; comparative legal, sociological. Results: the main approaches to the concept of communicative competence were analyzed, it was determined that communicative competence is a system of communicative knowledge, abilities, and skills that ensure effective legal communication of law enforcement officers with representatives of the state and civil society. The main characteristics of a law enforcement officer’s communicative competence are highlighted, including a system of knowledge on the theory and practice of communication; the ability to respond effectively in conflict situations; individual approach to the interlocutor; skills to establish contacts; the ability to conduct a constructive dialogue. Discussion: in the context of the integration of the Ukrainian law enforcement system into the international, in particular, European, growing demands from society for the activity of law enforcement agencies of Ukraine necessitates the search for ways to improve the communicative competence of law enforcement officers as an important component of their professionalism. Solving the practical tasks of forming the communicative competence of law enforcement officers will lead to the improvement of legal communication, will contribute to filling it with European experience, and the introduction of effective forms and methods of professional communication. Communicative competence is an important component of the professionalism of a law enforcement officer. The professional activity of a law enforcement officer requires the skills of effectively solving communication problems, drafting the texts of legal and procedural documents, and mastering the skills of conducting an effective discourse. Solving the practical tasks of forming the communicative competence of law enforcement officers will lead to the improvement of legal communication, will contribute to filling it with European experience, and the introduction of effective forms and methods of professional communication.